2021
DOI: 10.1080/22221751.2021.1959271
|View full text |Cite
|
Sign up to set email alerts
|

EasyNAT MTC assay: A simple, rapid, and low-cost cross-priming amplification method for the detection of mycobacterium tuberculosis suitable for point-of-care testing

Abstract: More sensitive, rapid, and affordable diagnostic tools for pulmonary tuberculosis (PTB) are urgently needed. This study aimed to assess the performance of EasyNAT MTC(abbreviation: EasyNAT) (Ustar Biotechnologies, China), a novel isothermal amplification method with a turnaround time of less than two hours that requires a few manual steps to process the sputum.Sputum samples from 249 patients with suspected PTB were subjected to smear, culture, Xpert MTB/RIF (Cepheid, USA) and EasyNAT assay testing. Of the 169… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…The first generation EasyNAT TB Isothermal Amplification Diagnostic Kit (EasyNAT TB IAD) and the next-generation EasyNAT MTC assay used here have been evaluated in the diagnosis of TB in adults ( Ou et al, 2014 ; Zhang et al, 2021 ). One study reported that the sensitivity of EasyNAT TB IAD in adults with culture-confirmed TB was 84.1% ( Ou et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first generation EasyNAT TB Isothermal Amplification Diagnostic Kit (EasyNAT TB IAD) and the next-generation EasyNAT MTC assay used here have been evaluated in the diagnosis of TB in adults ( Ou et al, 2014 ; Zhang et al, 2021 ). One study reported that the sensitivity of EasyNAT TB IAD in adults with culture-confirmed TB was 84.1% ( Ou et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that the sensitivity of EasyNAT TB IAD in adults with culture-confirmed TB was 84.1% ( Ou et al, 2014 ). The next-generation EasyNAT MTC assay performed in a clinical setting demonstrated an overall sensitivity of 72.19%, which further increased to 86.84% in cases with confirmed TB using sputum ( Zhang et al, 2021 ). Compared with these findings, the sensitivity of EasyNAT was lower in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If disease detection and treatment are delayed, the chance of transmission will increase (3). Therefore, rapid and accurate diagnosis of Mtb is an essential component of treating TB and reducing its global burden (4). Smear microscopy and culture are usually used as routine methods to detect Mtb in laboratories.…”
Section: Introductionmentioning
confidence: 99%